[Right ; left ; Center] - Lazaro, Cheche (The Probe Team, 1990)
Interview with Greg Honasan about the Rightist movement in military ; the left wing rebels, the Communist Movement in Quezon Province, AFP spokesmen on their offering to opposite ends of political spectrum and with other people, like the political analysts.